Hubungan Frekuensi Baby Spa Dengan Pertumbuhan Fisik Bayi Usia 6-12 Bulan Di Klinik Salsabila Mom & Baby Spa Kota Tangerang Tahun 2023 - Hanafiah , Iis; Idealistiana , Lia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Baby's weight is an indicator in measuring baby's growth. One of the supporting factors that really determines physical growth is providing stimulation using Baby Solus Per Aqua (SPA) because it can increase the baby's appetite and thus influence the baby's physical growth. It is said to be routine if baby SPA is done twice a week. Purpose of writing: To determine the relationship between the frequency of baby SPA and the physical growth of babies aged 6-12 months at the Salsabila Mom & Baby SPA Clinic, Tangerang City in 2023. Research Method: This research is a quantitative analytical research with a case sectional design. The sample in this study was 60 respondents aged 6-12 months, divided into two, namely 30 respondents for the case group and 30 respondents for the control group using total sampling technique. The research instrument uses an observation sheet. The data is primary data analyzed using the square test. Research Results: The results of the univariate analysis showed that 50.0% of babies aged 6-12 months routinely and non-routinely did baby SPA, most of the babies aged 6-12 months with physical growth increased by 61.7%. The results of the bivariate analysis showed a relationship between the frequency of baby SPA and the physical growth of babies aged 6-12 months with a p value of 0.008. Conclusions and Suggestions: there is a relationship between the frequency of baby SPA and the physical growth of babies aged 6-12 months. Mothers of babies are expected to increase their knowledge about the benefits and how to do baby SPA so that mothers can do massage at home independently and do it regularly so that the baby's growth is optimal.